2013
DOI: 10.1371/journal.pcbi.1003188
|View full text |Cite
|
Sign up to set email alerts
|

Distal Loop Flexibility of a Regulatory Domain Modulates Dynamics and Activity of C-Terminal Src Kinase (Csk)

Abstract: The Src family of tyrosine kinases (SFKs) regulate numerous aspects of cell growth and differentiation and are under the principal control of the C-terminal Src Kinase (Csk). Csk and SFKs share a modular design with the kinase domain downstream of the N-terminal SH2 and SH3 domains that regulate catalytic function and membrane localization. While the function of interfacial segments in these multidomain kinases are well-investigated, little is known about how surface sites and long-range, allosteric coupling c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Instrument setup and operation were described previously (26). All frozen samples were thawed and run using the conditions determined during fragmentation optimization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instrument setup and operation were described previously (26). All frozen samples were thawed and run using the conditions determined during fragmentation optimization.…”
Section: Methodsmentioning
confidence: 99%
“…The quality of each peptide was monitored by individually examining each measured isotopic envelope spectrum for the entire time-course exchange. The deuterium content was calculated for each time point by using specialized software as previously described (26,30).…”
Section: Methodsmentioning
confidence: 99%
“…To regulate the catalytic activity, such signals need to propagate from the protein’s regulatory sites to the ATP- and substrate-binding sites within the kinase domain. Although such communication has been explored previously 9 10 , the underlying mechanisms—and whether they lead to an allosteric interaction between the two binding sites—have not been completely elucidated, despite their importance for a better understanding of PTK regulation at a molecular level.…”
mentioning
confidence: 99%
“…Structural and dynamic studies of Csk have revealed the importance of maintaining optimal dynamics for efficient catalysis [ 26 28 ]. Perturbations to large global domain motions are likely to shift the exchange between solution state ensembles that can be detected via established solution methods [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…(His) 6 tagged Csk and kdSrc were expressed and purified as previously described [ 28 ]. Site-Directed mutagenesis was performed according to standard protocols.…”
Section: Methodsmentioning
confidence: 99%